The power of when : discover your chronotype--and the best time to eat lunch, ask for a raise, have sex, write a novel, take your meds, and more - Breus, Michael (Little, Brown and Company, 2016)
Most advice centers on what to do, or how to do it, and ignores the when of success. But exciting new research proves there is a right time to do just about everything, based on our biology and hormones. As Dr. Michael Breus proves in THE POWER OF WHEN, working with your body's inner clock for maximum health, happiness, and productivity is easy, exciting, and fun. THE POWER OF WHEN presents a groundbreaking new program for getting back in sync with your natural rhythm by making minor changes to your daily routine. After you've taken Dr. Breus's comprehensive Bio-Time Quiz to figure out your chronotype (are you a Bear, Lion, Dolphin or Wolf?), you'll find out the best time to do over 50 different activities. Featuring a foreword by Mehmet C. Oz, MD, and packed with fascinating facts, fun personality quizzes, and easy-to-follow guidelines, THE POWER OF WHEN is the ultimate "lifehack" to help you achieve your goals.--